Literary Figures, Academicians, Artistes Celebrates BH-UMP Riong Poetry Recital Night - UMP, PNC
Universiti Malaysia Pahang’s (UMP) first-ever We Care- “What’s My Sin?” campaign took off with the staging of a Poetry Recital Night, performed by well-known literary figures, academicians and famous artistes, with the concept of poetic lyrical songs to raise awareness and inculcate civic consciousness in addressing the social and moral decadence permeating the country, especially on the rising numbers of baby-dumping.